Detecção molecular do vírus Schmallenberg em abortos bovinos no Brasil - Costa, Marco Túlio dos Santos (2023)
First described in Germany in 2011, the Schmallenberg virus is important in livestock, asit can lead to spontaneous abortions and stillbirths, impacting the execution of revenue generated by animal production. Due to the lack of data on the occurrence of bovine abortion cases in Brazil, the objective of this work was to evaluate the occurrence of theSchmallenberg virus. There were 157 samples of aborted fetuses admitted to the Veterinary Hospital of the Federal University of Mato Groso, in the period from 2013 to 2022. The samples with macroscopic alterations compatible with the virus, the total nucleic acid ingestion were consumed and transmitted to RTqPCR for Schmallemberg virus. A total of seven samples were considered positive in the molecular test, five of which were followed up with a percentage of identity with the Schmallenberg virus. This study demonstrates that the Schmallenberg virus is circulating in Brazil, causing effects on animal production.